Annually Resolved Monsoon Onset and Withdrawal Dates Across the Himalayas Derived From Local Precipitation Statistics. Issue 23 (2nd December 2020) - Brunello, C. F.; Andermann, C.; Marc, O.; Schneider, K. A.; Comiti, F.; Achleitner, S.; Hovius, N.
Abstract: A local and flexible definition of the monsoon season based on hydrological evidence is important for the understanding and management of Himalayan water resources. Here, we present an objective statistical method to retrieve seasonal hydrometeorological transitions. Applied to daily rainfall data (1951–2015), this method shows an average longitudinal delay of 15 days, with later monsoon onset and earlier withdrawal in the western Himalaya, consistent with the continental progression of wet air masses. This delay leads to seasons of different length along the Himalaya and biased precipitation amounts when using uniform calendric monsoon boundaries. In the Central Himalaya annual precipitation has increased, due primarily to an increase of premonsoon precipitation. These findings highlight issues associated with a static definition of monsoon boundaries and call for a deeper understanding of nonmonsoonal precipitation over the Himalayan water tower. Plain Language Summary: Precipitation in the Himalayas determines water availability for the Indian foreland with large socioeconomic implications. Despite its importance, spatial and temporal patterns of precipitation are poorly understood. Here, we estimate the long‐term average and trends of seasonal precipitation at the scale of individual catchments draining the Himalayas. We apply a statistical method to detect the timing of hydrometeorological seasons from local precipitation measurements, focusing on monsoon onset and withdrawal. We identify longitudinal and latitudinal delays, resulting in seasons of different length along and across the Himalayas. These spatial patterns and the annual variability of the monsoon boundaries mean that oft‐used, fixed calendric dates, for example, 1 June to 30 September, may be inadequate for retrieving monsoon rainfall totals. Moreover, we find that, despite its prominent contribution to annual rainfall totals, the Indian summer monsoon cannot explain the increase of the annual precipitation over the Central Himalayas. Instead, this appears to be mostly driven by changes in premonsoon and winter rainfall. So far, little attention has been paid to premonsoon precipitation, but governed by evaporative processes and surface water availability, it may be enhanced by irrigation and changed land use in the Gangetic foreland. Key Points: We propose a new statistical definition of monsoon onset and withdrawal applicable a posteriori to daily precipitation time series Monsoon bounds show longitudinal delays and strong year‐to‐year variations, crossing commonly used seasonal calendric boundaries The long‐term increase of annual precipitation in Nepal seems to be driven primarily by higher premonsoon rainfall